2023
DOI: 10.1177/19714009231154681
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment findings on magnetic resonance imaging in primary central nervous system lymphoma may predict overall survival duration

Abstract: Background and purpose: Primary central nervous system lymphoma (PCNSL) lesions often show avid contrast enhancement on T1-weighted contrast-enhanced MRI sequences. However, several case reports and a clinical study have described PCNSL in patients with no contrast enhancement on MRI. We assessed whether overall survival (OS) time was related to any tumor characteristics (lesion location, volume, and number; contrast enhancement; necrosis; proximity to the subarachnoid space; and edema) on MRI in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In our study of patients with CNS lymphoma, we also found that higher volume on PET or enhanced T1weighted MRI sequence was a second independent biomarker of poor response to induction therapy and poor survival. Although tumor burden is well established as a prognostic factor in systemic lymphomas, data in the CNS setting is limited [39][40][41][42]. Our findings align with previous research by Albano et al, who reported in a study of 52 patients that patients with larger MTV had shorter PFS and OS [16].…”
Section: Discussionsupporting
confidence: 87%
“…In our study of patients with CNS lymphoma, we also found that higher volume on PET or enhanced T1weighted MRI sequence was a second independent biomarker of poor response to induction therapy and poor survival. Although tumor burden is well established as a prognostic factor in systemic lymphomas, data in the CNS setting is limited [39][40][41][42]. Our findings align with previous research by Albano et al, who reported in a study of 52 patients that patients with larger MTV had shorter PFS and OS [16].…”
Section: Discussionsupporting
confidence: 87%
“…[ 4 ] In the present case, the patient had an expansive intraparenchymal lesion in the subcortical white matter of the left temporal lobe with features suggestive of a lymphoproliferative tumor, but differentials such as secondary neoplastic processes and primary glial neoplasms could not be ruled out. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences after the initial response are common and generally occur within the CNS. [ 9 ] In contrast, the prognosis of relapsed disease is even worse, with a median OS of 2 months without therapy, and 7 months with it. [ 8 ] The 5-year OS rate is approximately 30%, and thus, new therapeutic approaches are necessary to improve these patients’ quality of life and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation